2014
DOI: 10.3109/14767058.2014.969235
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitamin D deficiency among pregnant women in a Turkish population and impact on perinatal outcomes

Abstract: This study has shown that maternal vitamin D deficiency is related with an increased risk of SGA delivery. Further studies are needed to explain the relationship with vitamin D deficiency and poor perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 24 publications
1
35
0
3
Order By: Relevance
“…The result of this process is a several-fold increase in serum vitamin D level in healthy pregnancy compared with the prepregnancy level [65]. However, the prevalence of vitamin D deficiency is increased among pregnant women, despite sufficient exposure to sunlight [66]. These data collectively suggest the supportive effect of pregnancy for anti-pancreatic β-cell autoimmunity development (in addition to underlying genetic susceptibility) [10,41,42].…”
Section: Pregnancy In Women At Risk Of T1d May Results In Autoimmune Gmentioning
confidence: 97%
See 1 more Smart Citation
“…The result of this process is a several-fold increase in serum vitamin D level in healthy pregnancy compared with the prepregnancy level [65]. However, the prevalence of vitamin D deficiency is increased among pregnant women, despite sufficient exposure to sunlight [66]. These data collectively suggest the supportive effect of pregnancy for anti-pancreatic β-cell autoimmunity development (in addition to underlying genetic susceptibility) [10,41,42].…”
Section: Pregnancy In Women At Risk Of T1d May Results In Autoimmune Gmentioning
confidence: 97%
“…The actions of IL-15 are modulated by vitamin D in many regulations, including maturation of adipocytes capable of producing adipokines [101]. However, the vitamin D level in pregnant women is commonly very low [66], which also affects calcium metabolism. In the presence of a low calcium level, 1,25(OH) 2 D 3 favors the expression of inflammatory cytokines (TNF-α, IL-6, IL-15) and inhibits the expression of anti-inflammatory cytokines (adiponectin) by adipocytes and muscle cells [102].…”
Section: Pregnancy In Women At Risk Of T2d May Results In Non-autoimmumentioning
confidence: 99%
“…One of the factors accepted as a regulator is vitamin D. In a study, small for gestational age probability was found to be 7.5 fold higher in the babies of the mothers with <15 ng/mL vitamin D levels23). But, on the other hand, there are also studies which did not find a relationship between the pregnancy vitamin D levels and birth weight and length.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2017) in a systematic review and meta-analysis, which included 5 cohort studies, [55][56][57][58][59] concluded that an extremely low 25(OH)D level (<20 ng/mL) was significantly associated with an increased risk of SA in the first trimester. Zhang et al (2017) in a systematic review and meta-analysis, which included 5 cohort studies, [55][56][57][58][59] concluded that an extremely low 25(OH)D level (<20 ng/mL) was significantly associated with an increased risk of SA in the first trimester.…”
Section: Introductionmentioning
confidence: 99%